Management In Prospering The Mosque Case Study At Alfurqon Mosque Karangjati Kemranjen Banyumas Central Java - Abdussalam, Sumin (Prosiding University Research Colloquium, 2021)
Mosques are the best places on earth. The mosque where the servants prostrate to Allah SWT. They pray, dhikr and do other worship. Good management is needed to carry out its functions properly. There are three main pillars in the management needed to prosper a mosque. They are making the mosque a center for Islamic and community activities; place of education and study, community information center; and the place of collection and distribution of zakat, infaq, and shadaqoh. In addition to management, no less important is human resources (HR). Thus we need cadres, cadres are the main assets that must be considered because they are the ones who will continue the Islamic struggle in the future. Al Furqon Mosque Karangjati Kemranjen Banyumas since the change of the mosque administrator in 2016 has begun to make improvements by learning to improve the management of how to prosper mosque, starting from mapping the area, collecting data on congregations, then making innovative programs. The service program as one of the programs at the Al Furqon Karangjati Mosque, Kemranjen Banyumas is the Fajr Bank program, that is collecting infaq at the time of Fajr prayer then allocate the infaq as soft loans ( primarily for them who are Fajr congregation), financial support for when they are sick, providing free ambulance services and then financing and arranging the funeral and burial for the deceased concregations or their relatives. With service improvement and good quality programs, the number of congregations praying five times a day and assemblies ta’lim increases.